2011
DOI: 10.1002/hlca.201000378
|View full text |Cite
|
Sign up to set email alerts
|

Flavone 8‐C‐Glycosides from Haberlea rhodopensisFriv. (Gesneriaceae)

Abstract: Phytochemical profiling of a MeOH extract from Haberlea rhodopensis by a combination of liquid/liquid extraction, and preparative and semi‐preparative HPLC afforded three new flavone C‐glycosides, hispidulin‐8‐C‐(2″‐O‐syringoyl)‐β‐glucopyranoside (3), hispidulin 8‐C‐(6‐O‐acetyl‐β‐glucopyranoside) (4), and hispidulin 8‐C‐(6‐O‐acetyl‐2‐O‐syringoyl‐β‐glucopyranoside) (5), along with two known phenolic glycosides, myconoside (1) and paucifloside (2). The structures were established by extensive spectroscopic analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(31 citation statements)
references
References 19 publications
0
24
0
Order By: Relevance
“…The obtained data matrix of peak area was normalized using the internal standard (isovitexin, CAS: 29702-25-8). Metabolite identification and annotation were performed using metabolite databases [34] and literature survey of H. rhodopensis [35] and Gesneriaceae species [36]. Peak annotation of detected compounds is shown in Supplemental Table 5 with information on ''Recommendations for Reporting Metabolite Data'' described in [37].…”
Section: Metabolome Analysismentioning
confidence: 99%
“…The obtained data matrix of peak area was normalized using the internal standard (isovitexin, CAS: 29702-25-8). Metabolite identification and annotation were performed using metabolite databases [34] and literature survey of H. rhodopensis [35] and Gesneriaceae species [36]. Peak annotation of detected compounds is shown in Supplemental Table 5 with information on ''Recommendations for Reporting Metabolite Data'' described in [37].…”
Section: Metabolome Analysismentioning
confidence: 99%
“…The presence of flavonoids and tannins, due to the limitations of GC -MS, was not detected (Berkov et al 2011). Phytochemical profiling of methanol extract from H. rhodopensis by combination of liquid/liquid extraction, preparative and semi-preparative HPLC showed two known phenolic glycosides, myconoside and paucifloside, together with three new flavone C-glycosides, hispidulin-8-C-(2 00 -O-syringoyl)-bglucopyranoside, hispidulin 8-C-(6-O-acetyl-b-glucopyranoside), and hispidulin 8-C-(6-Oacetyl-2-O-syringoyl-b-glucopyranoside) (Ebrahimi et al 2011), later confirmed by KondevaBurdina et al (2013). Thus, the biologically active compounds in H. rhodopensis are intensively studied and these experiments should continue further.…”
Section: Biologically Active Compoundsmentioning
confidence: 99%
“…The phytochemical profiling of methanol extract from H. rhodopensis, by using a combination of liquid/liquid extraction, preparative and semi-preparative HPLC, revealed flavone C-glycosides hispidulin-8-C-(2 00 -O-syringoyl)-b-glucopyranoside, hispidulin 8-C-(6-Oacetyl-b-glucopyranoside), hispidulin 8-C-(6-O-acetyl-2-O-syringoyl-b-glucopyranoside), as well as phenolic glycosides myconoside and paucifloside (Ebrahimi et al 2011). A specific fraction was rich in myconoside, a caffeoyl phenylethanoid glycoside with a potential role in the plant survival (Dell'Acqua & Schweikert 2012).…”
Section: Antioxidant Potential and Free Radical-scavenging Activitymentioning
confidence: 99%
See 2 more Smart Citations